Food Security as a Multidimensional Construct: From a Six-Dimensional Framework to an Integrated Measurement Architecture - Loso Judijanto (PT. Anagata Sembagi Education, 2026)
Food security can no longer be adequately understood or measured through food availability alone because climate shocks, price volatility, conflict, unequal access, dietary change, and ecological pressures operate simultaneously across food-system scales. This article synthesizes the recent evolution of food-security theory, explains the extension of the four classical dimensions to a six-dimensional framework comprising availability, access, utilization, stability, agency, and sustainability, and examines the resulting implications for measurement. An interpretive and thematic qualitative literature review was conducted using peer-reviewed journal articles published from 2020 to 2026. The synthesis shows that food security is a multidimensional, multiscalar, and dynamic construct for which no single indicator can provide a valid representation. A stronger measurement strategy combines household experience measures, healthy-diet affordability, production and price indicators, diet and nutrition outcomes, shock exposure and recovery, agency, and socio-ecological sustainability. The article therefore proposes a layered measurement architecture in which a multidimensional dashboard is the primary diagnostic instrument and composite indices are used only for clearly defined policy purposes with transparent weights and assumptions. For Indonesia, spatial, social, livelihood, and temporal disaggregation is essential because vulnerability varies markedly across an archipelagic and highly diverse food system. Future research should validate agency and sustainability measures, expand longitudinal and spatial integration, and test policy trade-offs across dimensions.